Secondary distribution of HIV self-test kits by HIV index and antenatal care clients: implementation and costing results from the STAR Initiative in South Africa - Vincent Zishiri; Donaldson F. Conserve; Zelalem T. Haile; Elizabeth Corbett; Karin Hatzold; Gesine Meyer-Rath; Katleho Matsimela; Linda Sande; Marc d’Elbee; Fern Terris-Prestholt; Cheryl C. Johnson; Thato Chidarikire; et al. (BMC Infectious Diseases, 2023)
Abstract Background Partner-delivered HIV self-testing kits has previously been highlighted as a safe, acceptable and effective approach to reach men. However, less is known about its real-world implementation in reaching partners of people living with HIV. We evaluated programmatic implementation of partner-delivered self-testing through antenatal care (ANC) attendees and people newly diagnosed with HIV by assessing use, positivity, linkage and cost per kit distributed. Methods Between April 2018 and December 2019, antenatal care (ANC) clinic attendees and people or those newly diagnosed with HIV clients across twelve clinics in three cities in South Africa were given HIVST kits (OraQuick Rapid HIV-1/2 Antibody Test, OraSure Technologies) to distribute to their sexual partners. A follow-up telephonic survey was administered to all prior consenting clients who were successfully reached by telephone to assess primary outcomes. Incremental economic costs of the implementation were estimated from the provider’s perspective. Results Fourteen thousand four hundred seventy-three HIVST kits were distributed – 10,319 (71%) to ANC clients for their male partner and 29% to people newly diagnosed with HIV for their partners. Of the 4,235 ANC clients successfully followed-up, 82.1% (3,475) reportedly offered HIVST kits to their male partner with 98.1% (3,409) accepting and 97.6% (3,328) using the kit. Among ANC partners self-testing, 159 (4.8%) reported reactive HIVST results, of which 127 (79.9%) received further testing; 116 (91.3%) were diagnosed with HIV and 114 (98.3%) initiated antiretroviral therapy (ART). Of the 1,649 people newly diagnosed with HIV successfully followed-up; 1,312 (79.6%) reportedly offered HIVST kits to their partners with 95.8% (1,257) of the partners accepting and 95.9% (1,206) reported that their partners used the kit. Among these index partners, 297 (24.6%) reported reactive HIVST results of which 261 (87.9%) received further testing; 260 (99.6%) were diagnosed with HIV and 258 (99.2%) initiated ART. The average cost per HIVST distributed in the three cities was US$7.90, US$11.98, and US$14.81, respectively. Conclusions Partner-delivered HIVST in real world implementation was able to affordably reach many male partners of ANC attendees and index partners of people newly diagnosed with HIV in South Africa. Given recent COVID-19 related restrictions, partner-delivered HIVST provides an important strategy to maintain essential testing services.